HUBUNGAN INTENSITAS MENONTON DRAMA KOREA DAN TINGKAT KESUKAAN MUSIK POP KOREA DENGAN MINAT BELAJAR BAHASA KOREA PADA REMAJA - Naomi Feby Yolanda Br Saragih; S. Rouli Manalu; Djoko Setyabudi (Interaksi Online, 2023)
This study aims to determine the relationship between the intensity of watching Korean dramas and the level of liking Korean pop music with interest in learning Korean in adolescents. This is motivated by the fact that Indonesia is one of the countries hit by the Korean Wave phenomenon. Various products from the Land of Gingseng have successfully entered Indonesia and are favored in all circles. Korean dramas, Korean pop music and the Korean language are the Korean Wave products that attract the most attention and interest. The three phenomena occur at the same time but it is not known whether the three phenomena are interconnected. The study used Uses and Gratification theory and was conducted with purposive nonprobability sampling technique, with 100 samples aged 18-25 years in Semarang city. The results showed that there is a positive relationship between the intensity of watching Korean dramas and interest in learning Korean. This means that the higher the intensity of watching Korean dramas, the higher the interest in learning Korean. Furthermore, there is a positive relationship between the level of liking for Korean pop music and interest in learning Korean, which means that the higher the level of liking for Korean pop music, the higher the interest in learning Korean. This shows that Korean drama, Korean pop music and Korean language are interconnected phenomena and proves that the desire to learn a particular language or culture can be started by providing popular culture such as drama series and music.